Variasi Warna Dan Ketinggian Sticky Trap Dengan Atraktan Methyl Eugenol Sebagai Pengikat Serangga Polinator Dan Serangga Lainnya Pada Musim Bunga Pohon Jambu Air Merah Delima - Tarwotjo, Udi; Hadi, Mochamad; Rahadian, Rully (Bioma : Berkala Ilmiah Biologi, 2019)
The objective of this research was to determine the effectiveness of color and height variation of sticky trap with methyl eugenol on Insect visitting of flowers and other insect on apple water tree in Demak. Sampling of insects was conducting in one of apple water field in Demak using sticky trap with methyl eugenol attractant . There were three different colors of sticky trap and two height variation of trap placement were used. The data was analysed using descriptive analysis. Parameters observed included the number of fruit flies in each color, height of sticky trap, and the family of insects. The results showed that the insects found consist of 5 orders and 21 families. (Diptera, Hymenoptera, and Coleoptera, Lepidoptera, and Homoptera). . Most families are found in the order Diptera (8 families), Hymenoptera (6 families), Coleoptera (3 families), and Homoptera (4 families). The Diptera family consists of Tephritidae, Culicidae, Agromyzidae, Muscidae, Asillidae, Mycetophyllide, Drosophyllidae, Bombyllidae. The conclusion of this research is that the control of inseks visitting by using bright color sticky trap (yellow and white) with methyl eugenol attractant can be used as a trap of insect vistting of Diptera and other insects in the largest number of families